La tolerancia activa en Voltaire (2020)
The purpose of this article is to elucidate the human rights crisis, identified in Voltaire's work, specifically in three of his books: English letters or Philosophical letters; Philosophical dictionary, and especially; Treaty on tolerance, in which it is identified as a central problem: "religious intolerance", behavior that triggers the violation of a plurality of subjective rights. To get out of the problem, the philosopher proposes active tolerance, which implies putting into practice a dialogue between the various sectors in conflict for religious differences, which will seek to reach agreements that put an end to the conflict.